2017
DOI: 10.1016/j.bbadis.2016.09.012
|View full text |Cite|
|
Sign up to set email alerts
|

CD95-mediated apoptosis in Burkitt's lymphoma B-cells is associated with Pim-1 down-regulation

Abstract: B-cells of the high-grade non-Hodgkin lymphoma Burkitt's lymphoma (BL) overexpress survival oncoproteins, including the proviral integration site for Moloney murine leukaemia virus kinase (Pim)-1, and become apoptosis resistant. Activated death receptor CD95 after ligation with anti-CD95 monoclonal antibody (mAb) resulted in the regression of BL via induction of apoptosis, suggesting a decrease of survival protein expression. Here, CD95-mediated apoptotic pathways in BL B-cell lines (Raji and Daudi) following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…This suggested that upregulation of PIM-1 may promote the disruption of cell proliferation and homeostasis to drive malignant aggression and lead to a poor outcome. Dysregulation of apoptosis is a vital feature of oncogenes and a number of previous studies have revealed that PIM-1 has an important role in apoptosis (18)(19)(20). The present study demonstrated that the apoptotic rate had a significant association with PIM-1 expression level in ACC patients' tissues.…”
Section: Discussionsupporting
confidence: 65%
“…This suggested that upregulation of PIM-1 may promote the disruption of cell proliferation and homeostasis to drive malignant aggression and lead to a poor outcome. Dysregulation of apoptosis is a vital feature of oncogenes and a number of previous studies have revealed that PIM-1 has an important role in apoptosis (18)(19)(20). The present study demonstrated that the apoptotic rate had a significant association with PIM-1 expression level in ACC patients' tissues.…”
Section: Discussionsupporting
confidence: 65%
“…After the protein extraction from the untreated and treated TNBC MDA-MB-231 cells, 35 pro-apoptotic and anti-apoptotic proteins were detected, using the Proteome Profiler Human Apoptosis Protein Array kit (Life Technologies) and analyzed, as described in. 34…”
Section: Methodsmentioning
confidence: 99%
“…After the protein extraction from the untreated and treated TNBC MDA-MB-231 cells, 35 pro-apoptotic and anti-apoptotic proteins were detected, using the Proteome Profiler Human Apoptosis Protein Array kit (Life Technologies) and analyzed, as described in. 34 From cell lysis to the separation, by molecular weight, of the extracted proteins on 12% SDS-PAGE gel electrophoresis, Western blot technology was done as described in. 35 Provided by Abcam (Cambridge, UK), mouse monoclonal antibody against pro-and active cleaved-caspase-3 [ABM1C12], rabbit monoclonal antibody against p21 [EPR3993] (1:1000) and mouse monoclonal antibody against GAPDH (1:2000), were used as the primary antibodies for the detection of the targeted proteins.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…4309155; Qiagen GmbH), using the 7900 Fast Real-Time PCR system (Thermo Fisher Scientific, Inc.). The primer pair sequences (Invitrogen; Thermo Fisher Scientific) were used as previously described ( 12 ). The thermocycling conditions were as follows: Heat denaturing at 95°C for 10 min, then by 40 cycles of denaturing at 95°C for 10 sec followed by annealing at 57°C for 20 sec and finally extension at 72°C for 30 sec.…”
Section: Methodsmentioning
confidence: 99%